INTEGRASI BASIS DATA SYARAT MUTLAK PEMBANGUNAN SISTEM INFORMASI E-GOVERNMENT - Wimmie Handiwidjojo; Budi Suteja Dharma Oetomo (Seminar Nasional Informatika (SEMNASIF), 2009)
Starting from the case of the final voter list in the Indonesia parliamentary election 2009, which made many Indonesian voters could not give his choice, the government should know that the implementation of e- Government based on the Information Technology has not been managed well yet. The managing of e- Government has been far away from the goal. Developing of e-Government does not mean building the government web site, which provide information in a static webpage, but it depends on some aspects such as information system design that used to manage data, database design and the computer network infrastructure that has been used. The method of developing information system for e-Government in Indonesia has been done step by step and partially, where every department developed its own IT system.. The developing of IT system in each department was not base on the integrated IT blue print of the Indonesia Government. It has not been planned well. The results of this caused the integration of the database is being difficult. The blue print is very important for making a standard of data format, coding, type of DBMS, protocol, etc. When the Indonesia e-Government was built on a good information system design and based on an integrated database standard, hopefully the problem of the final voter list would not occur in this Indonesia parliamentary election 2009.